Allele-specific regulation of MTTP expression influences the risk of ischemic heart disease[S] - Aminoff, Anna; Ledmyr, Helena; Thulin, Petra; Lundell, Kerstin; Nunez, Leyla; Strandhagen, Elisabeth; Murphy, Charlotte; Lidberg, Ulf; Westerbacka, Jukka; Franco-Cereceda, Anders; Liska, Jan; Nielsen, Lars Bo; et al. (Journal of lipid research, 2010)
Promoter polymorphisms in microsomal triglyceride transfer protein (MTTP) have been associated with decreased plasma lipids but an increased risk for ischemic heart disease (IHD), indicating that MTTP influences the susceptibility for IHD independent of plasma lipids. The objective of this study was to characterize the functional promoter polymorphism in MTTP predisposing to IHD and its underlying mechanism. Use of pyrosequencing technology revealed that presence of the minor alleles of the promoter polymorphisms -493G>T and -164T>C result in lower transcription of MTTP in vivo in the heart, liver, and macrophages. In vitro experiments indicated that the minor -164C allele mediates the lower gene expression and that C/EBP binds to the polymorphic region in an allele-specific manner. Furthermore, homozygous carriers of the -164C were found to have increased risk for IHD as shown in a case-control study including a total of 544 IHD patients and 544 healthy control subjects. We concluded that carriers of the minor -164C allele have lower expression of MTTP in the heart, mediated at least partly by the transcription factor CCAAT/enhancer binding protein, and that reduced concentration of MTTP in the myocardium may contribute to IHD upon ischemic damage.